The impact of international investment on the economic situation in Syria (Latakia University Journal - Economic and Legal Sciences Series, 2021)
This study aimed to show the impact of international investment on economic indicators in Syria, where the researcher relied on the descriptive and analytical approach to the reality of international investment in Syria.Among the most important results reached by the researcher:- There is a statistically significant effect of international investment on the gross domestic product in Syria.- There is a statistically significant effect of international investment on exports in Syria.- There is a statistically significant effect of international investment on imports in Syria.